Numerical study of fracture arrest on snow cover - B. M. Chiaia; B. Frigo (Fracture and Structural Integrity)
Under the hypothesis of a perfectly brittle phenomenon, avalanche triggering can be investigated numerically by means of Linear Elastic Fracture Mechanics (LEFM). Since, however, the real phenomenon is intrinsically dynamical, another aspect to investigate is represented by dynamic fracture propagation. In this paper, we model dynamic crack propagation into a dry snow slab and we investigate the possibility to arrest the crack propagation through the presence of weak zones distributed along the extension of the snow slope. Assuming that the weak layer is almost collapsed, we simulate the efficiency of artificial voids in the slab to arrest fracture propagation, into the framework of Dynamical Fracture Mechanics. We put forward here a new philosophy for the use of artificial discontinuities (void) into the snowpack able to perform as crack arresters  distributed along the snow slope area: the target is to split a large avalanche slab into smaller slabs, causing small avalanches to propagate with less catastrophic effects.